CIO inventory: A new tool for measuring personality traits common to psychopathy and narcissism and their interaction with gender. (July 2018) - Carraro, Luciana; Spironelli, Chiara; Poli, Eleonora; Bobbio, Andrea; Castelli, Luigi; Arcuri, Luciano; Angrilli, Alessandro
Abstract: A lack of empathy, interpersonal dominance, aggression and the exploitation of others are the key features of both narcissism and psychopathic disorders. With the aim to better capture the shared facets of these traits, this study developed a new tool named the Capability to Influence Others (CIO) Inventory, which is based on the pleasantness evaluation of ten items–verbs presented in the infinitive form. The inventory, characterized by very quick submission, was administered to 67 males and 100 females and was correlated with the concurrent Narcissistic Personality Inventory (NPI) and Levenson Self-Report Psychopathy Scale (LSRP). An exploratory factor analysis supported the presence of only one factor in both the male and female groups. Internal consistency of the CIO was very good for both men (Cronbach's alpha = 0.85; 95% CIs: 0.80–0.90) and women (Cronbach's alpha = 0.83; 95% CIs: 0.77–0.87). Further statistics showed a high correlation between the CIO and the LSRP-F1 (primary psychopathy) in both genders ( r  > 0.47). Clear gender differences were found in the correlation between the CIO and the NPI: the correlation was high ( r  = 0.58) in males and absent in females. The CIO may represent a quick and low demanding tool for a preliminary screening of individuals with high psychopathic/narcissistic traits from community samples, forensic institutions, high schools and company personnel. Highlights: The CIO inventory requires to judge the pleasantness of 10 infinitive verbs. The CIO inventory has been correlated with narcissism and psychopathy traits. Primary psychopathy assessed by LSRP was correlated with CIO in both men and women. Narcissism assessed with NPI was highly correlated with CIO in men, not in women. CIO revealed to be a quick and less demanding tool well correlated with psychopathy.